천식과 만성폐쇄성폐질환 중복(Asthma-COPD Overlap) 환자에 대한 복합 한의치험 1례 - 진수현; 박지원; 신정원; 이범준; 정희재; 김관일; Su-hyun Chin; Ji-won Park; Jeong-won Shin; Beom-joon Lee; Hee-jae Jung; Kwan-il Kim (대한한방내과학회지, 2024)
Background: Asthma and chronic obstructive pulmonary disease (COPD) both require long-term management, and patients with asthma-COPD overlap (ACO) need comprehensive and prolonged care beyond pharmacotherapy. However, due to limited research on ACO, treatment strategies and long-term outcomes remain unclear. This highlights the need for further multidisciplinary research to improve ACO treatment and prognosis. Case Presentation: This case report describes a patient who presented with symptoms of cough, sputum, wheezing, dyspnea, and oral dryness. The patient was diagnosed with ACO and received a combination of Korean medicine treatments alongside standard asthma medication for 15 days. Standardized tools were used to evaluate symptoms and quality of life, respectively. After treatment, Medical Research Council scale, Leicester cough questionnaire Korean-Version and Numerical Rating Score demonstrated clinically meaningful improvement, and Total IgE and Eosinophils were slightly decreased. Conclusion: This case suggests Korean medicine treatments might be effective in managing symptoms in patients with ACO and enhancing quality of life.